Deposition of the stoichiometric coatings by reactive magnetron sputtering - Sagalovych, A.; Dudnik, S.; Sagalovych, V. (Физическая инженерия поверхности, 2012)
The investigations of the reactive magnetron depositing of the stoichiometric coatings “metal-metalloid” were done. The dependences between sputtering parameters of a target and processes of plasmochemical formation on the surface of sample “metal-metalloid” and formations of coatings of the appropriate structure were investigated. Experimental data on stoichiometric coatings AlN, Al₂O₃, TiN, TiO₂ is given. Features of reactive magnetron deposition and investigation results for obtaining of coatings with pregiven properties in particular for providing stability and controllability of coating deposition processes in time.